Rubisco small subunits of C4 plants, Napier grass and guinea grass confer C4-like catalytic properties on Rubisco in rice - Hiroshi Fukayama; Takashi Kobara; Keita Shiomi; Ryutaro Morita; Daisuke Sasayama; Tomoko Hatanaka; Tetsushi Azuma (Plant Production Science, 2019)
Overexpression of Rubisco small subunit (RbcS) of C4 plant, sorghum (sorghum bicolor) was shown to enhance the catalytic turnover rate (kcat) of Rubisco in rice (Oryza sativa). In this study, the effects of other Rubisco small subunits of C4 plants, Napier grass (Pennisetum purpureum) and guinea grass (Megathyrsus maximus) on kinetic properties of Rubisco in rice were studied. The expression levels of Napier grass RbcS (NgRbcS) and guinea grass RbcS (GgRbcS) proteins accounted for 41% and 45% of total RbcS, respectively in homozygous overexpression lines. The kcat and Km for CO2 (Kc) of Rubisco were increased in all transgenic lines. Interestingly, the kcat was markedly higher in NgRbcS homozygous line, whereas Kc was notably higher in GgRbcS homozygous line. Although its effects depend on species, these results suggest that the introduction of C4 RbcS are effective approaches to alter the catalytic properties of Rubisco in rice. Abbreviation GgRbcS: guinea grass RbcS; Kc: Km for CO2; kcat: catalytic turnover rate; NpRbcS: Napier grass RbcS; RbcL: Rubisco large subunit; RbcS: Rubisco small subunit; Sc/o: CO2/O2 specificity.